Development of latex / silica aerogel composites for thermal insulation applications - Samuel Pantaleo; Florent Gauvin; Katrin Schollbach; H.J.H. Brouwers (Developments in the Built Environment)
Silica aerogel stands out as an exceptional thermal insulation material and is a great candidate for modern and energy-efficient buildings. However, silica aerogel also faces many challenges, mainly due to its expensive, unsustainable and difficult synthesis process, but also its poor structural properties. Consequently, the main research focus for silica aerogel is to mitigate its brittleness in order to pave the way for broader applications, especially in the building field. Therefore, this study focuses on the development of composite materials aiming at solving the abovementioned drawbacks of silica aerogel, by using environmentally friendly latexes and reinforcement that are easy to process. Results show the positive effect of this reinforcement, even at a small amount (5% volume), on the composite's properties, with thermal conductivity at least equivalent, or better, to either in development or already established insulation materials in the market.